Methods of measurements of the quality factor of piezoelectric resonators with high electrical and mechanical losses - W. PAJEWSKI; M. SZALEWSKI (Archives of Acoustics, 2014)
In the paper the analysis of methods of measurements of the piezoelectric resonators quality factors has been presented, as well as the possibility of their applications for resonators with high electrical and mechanical losses, e.g. ceramics and piezoelectric foils. The problem of the quality factor measurements for resonators excited by high electric field has been also discussed. To this end the authors propose to apply a ring-shaped piezoelectric transformer. This metod enables us to measure ceramic parameters in the quasi-linear range, to separate mechanical and electrical losses, and to determine the range of the linear work. The conducted analysis makes it possible to conclude the lack of a precise method of the quality factor and also the losses measurement for piezoelectric resonators with low quality factors, also in the case when nonlinear effects occur.